Examination of Library Spaces in the Context of the Third Place Paradigm of Oldenburg - Demir, Güler (Information World, 2017)
Space and related concepts are of interdisciplinary nature, and are not trivial to define due to their broad and complex meanings. The observations and perception by an architect, a planner, or a designer of a particular space will likely differ from those by a geographer, an anthropologist, an ecologist or a social science expert. Furthermore, thoughts and feelings of the individual(s) who use the space can add new aspects to this perception. If the common goal for all disciplines is to construct and/or develop optimized spaces, one of the most important / determining factors of quality of life, it is ideal to carefully evaluate all perspectives.In this study, it is aimed to discuss library space in the context of city sociologist Ray Oldenburg’s paradigm, conceptualized as “third space”. Descriptive method with a comprehensive literature search is used in this study. In conclusion, a library with “third space” characteristics can be a strong alternative to the concern that the spatial dimension of the library or its services aimed at the information society shaped by the changing technology world would blur or even disappear.
Keywords: Ray Oldenburg; third space; urban sociology; public space; environment; library services; makerspace